Avaliação fisiológica e anatômica dos efeitos da deposição de ferro e dióxido de enxofre em duas espécies vegetais ocorrentes na restinga : Schinus terebinthifolius e Mimusopsis coriacea - Lopes, Sandrelly Amigo (2005)
The objective is to analyze the effects of the settling of iron particles and of sulphur dioxide on the growth, on the physiological parameters and morphological and histo-chemical parameters, aiming at active bio monitoring. Schinus terebinthifolius (Anacardiaceae) and Mimusopsis coriacea (Sapotaceae) seedlings were exposed during an eight-month period to the gas and particle emissions of a pelletizing plant located in the municipal region of Anchieta, State of Espirito Santo. The plant species were selected because of what they represent in the lowlands environment, and because they are used for the purpose of planting trees in urban areas. These species’ uncomplicated planting care, as well as their morphological, phonologic and physiological characteristics, were also taken into consideration. Two experiments were conducted. In the first experiment, the species were placed in standard stations and spread throughout a transect according to the predominant wind direction in the region and at different distances: 200 meters, 500 meters, 800 meters, 1,400 meters and 1,700 meters away from the source of the emissions. The second experiment focused on temporal evaluation conducted at a station located in a product stocking and handling yard and in a reference area. Analyses were made of the trees’ height, the number of leaves, and the number and percentage of dead leaves, the foliar phyto-toxic chlorosis index, the foliar temperature, the temperature-related difference and the air, and the sedimentary dust content. The following data was analyzed on the last data gathering date: the settling of iron on the leaves, the iron and the sulphur content of the leaves, stems and roots, the chlorophyll a and b content, the gas exchange and the total dry mass of the plant material. In the second experiment, these analyses were conducted monthly, and included the number of flowering or non-flowering events, and the number of fruit or branches with fruit. The highest deposits of iron particles were verified at 200 meters. A higher quantity of settled iron particles per leaf area unit was observed at this same distance in the two species, S. terebinthifolius and M. coriacea. The highest foliar contents of total iron were verified at 200 meters in both plant species; that is, at the station located closest to the pelletizing plant, showing a gradual reduction as the distance from the emission source increased. The highest iron contents were found in the roots of both species. The highest content of total sulphate was observed in the M. coriacea, at 200 meters and in the S. terebinthifolius at 500 meters away from the emission source. There is a positive correlation between the foliar area and the settling of iron. No height-related variations were verified in the two species. The percentage of dead leaves was verified only in the S. terebinthifolius species lying at 500 meters and 800 meters away from the source. The number and the percentage of dead leaves and the necrosis phyto-toxicity index in the two species increased as exposure time to the plant’s emissions was extended. The same event was verified in the M. coriacea species lying 800 meters and 1,400 meters away from the source. A higher necrosis-related phyto-toxicity index of the M. coriacea was verified in the exposed plants located 200 meters and 1,400 meters away, whereas the highest such index for the S. terebinthifolius species was verified in the plants located 1,400 meters away. The pigment content of both species did not change because of the distance from the emission source. However, a slight reduction in the content of a and b chlorophyll and in the carotene content was verified at 800 meters. In general, the gas exchanges, that is, the reduction of the stoma conductance of the 11 transpiration and the liquid assimilation of CO2 in the S. terebinthifolius and M. coriacea, were lower at the stations located next to the plant. In other words, the related levels were generally lower at the stations lying closer to the emission source. M. coriacea proved to be more sensitive, with symptoms of damage to fluorescence at 200, 500 and 1,400 meters, whereas in relation to S. terebinthifolius, reduced damage was evidenced at 500 meters. In relation to the histo-chemical test, S. terebinthifolius accumulated higher amounts of iron with higher settling at the reentering angles at the bases of the uni-serial glandular trychomas, while M. coriaceae had a lower iron content, probably because of the leaves’ arrangement and smooth texture, the stomas hollows, the existence of thick hypodermis and cuticles on both sides of the leaves, acting as protection mechanisms to prevent the entry of polluting agents. As for the second experiment, there was higher settling of particles on the surface exposed to industrial activities conducted at the product stocking and handling yard, in contrast to the surface that had not been exposed. The exposed plants contained higher settlement and accumulation of iron in the case of both species. The settling and accumulation of iron increased in the S. terebinthifolius species during the exposure period, as did the number of this species’ leaves. This increase was verified to a greater extent at the station located in the industrial yard. This was not evidenced in relation to M. coriacea. Settling was reduced because of the rainy season. As for iron absorption, there was an increase, in general terms, for a period of two months after exposure to the facility. The figures related to iron accumulation in the plants exposed to the industrial area were higher for both species. Most of the accumulated iron was verified mainly in the roots of both species. A general increase in the content of plant species material was verified in both species. The growth in this material in S. terebinthifolius was verified in the industrial yard, while this growth in M. coriacea was verified in an area that had not been exposed to atmospheric emissions. There was no temporal variation in the height of the M. coriacea at the two stations, whereas there was more pronounced exponential growth of this material in the S. terebinthifolius located at the industrial yard. The quantity of flowers and fruit was significantly reduced on plants exposed to industrial conditions. The incidence of damage, measured according to the percentage of necrosis and to the phyto-toxicity index, was higher in the areas exposed to industrial emissions. Damage increased gradually in both species in relation to exposure time. There was no variation in the chlorophyll or in the carotenoids. The figures related to transpiration and stoma conductance in general were higher in the exposed areas. S. terebinthifolius and M. coriacea had higher CO2 assimilation rates throughout the exposure period and on the non-exposed area. Fluorescence for the two species was more affected during the month of August, probably as a result of the iron that had been absorbed and of the accumulation of iron particles in July, which were absorbed in the roots as a result of the rainfall in that month. According to histo-chemical tests, the species accumulated more iron on the exposed area and the S. terebinthifolius species accumulated higher quantities of iron than the M. coriacea did because of the former species’ morphological and anatomical characteristics, as mentioned above. M. coriacea was the more sensitive of the species. Both species are reaction bio indicators, and can be used in active bio indication. S. terebinthifolius is a resistant species that can be used in the reclaiming of areas damaged by mining activities because of its rapid growth rate and gene-typical plasticity.